Using system dynamics modeling to evaluate a community-based social marketing framework: A computer simulation study. Issue 1 (17th December 2018) - Biroscak, Brian Joseph; Bryant, Carol; Khaliq, Mahmooda; Schneider, Tali; Panzera, Anthony Dominic; Courtney, Anita; Parvanta, Claudia; Hovmand, Peter
Abstract : Purpose: Community coalitions are an important part of the public milieu and subject to similar external pressures as other publicly funded organizations – including changes in required strategic orientation. Many US government agencies that fund efforts such as community-based social marketing initiatives have shifted their funding agenda from program development to policy development. The Florida Prevention Research Center at the University of South Florida (Tampa, Florida, USA) created community-based prevention marketing (CBPM) for policy development framework to teach community coalitions how to apply social marketing to policy development. This paper aims to explicate the framework's theory of change. Design/methodology/approach: The research question was: "How does implementing the CBPM for Policy Development framework improve coalition performance over time?" The authors implemented a case study design, with the "case" being a normative community coalition. The study adhered to a well-developed series of steps for system dynamics modeling. Findings: Results from computer model simulations show that gains in community coalition performance depend on a coalition's initial culture and initial efficiency, and that only the most efficient coalitions' performance might improve from implementing the CBPM framework. Originality/value: Practical implications for CBPM's developers and users are discussed, namely, the importance of managing the early expectations of academic-community partnerships seeking to shift their orientation from downstream (e.g. program development) to upstream social marketing strategies (e.g. policy change).